New Spiroplasma in parasitic Leptus mites and their Agathemera walking stick hosts from Argentina - DiBlasi, Emily (2011)
Here we report the presence of Spiroplasma 16S rRNA in populations of two parasitic Leptus mites (Leptus sayi; Leptus lomani) and their Agathemera walking stick hosts. In walking sticks Spiroplasmas were detected in the gut, as well as muscle-tissues, but not in eggs. Throughout Argentina 15.4% of L. sayi populations and 14.3% of L. lomani populations surveyed screened positive for Spiroplasma. Phylogenetic analyses (ML, BCMC) place all sequences within the Ixodetis group. Most sequences form a well-supported sister subclade to the rest of Ixodetis. We briefly discuss the role of Leptus mites in the natural transmission of Spiroplasma.